AA amyloidosis complicating monoclonal gammopathies, an unusual feature validating the concept of "monoclonal gammopathy of inflammatory significance"?. Issue 11 (21st September 2021) - Terré, Alexandre; Colombat, Magali; Cez, Alexandre; Martin, Claire; Diet, Carine; Brechignac, Sabine; Oghina, Silvia; Bodez, Diane; Faguer, Stanislas; Savey, Léa; Galland, Joris; Boffa, Jean‐Jacques; et al.
Abstract: Introduction: AL amyloidosis is caused by the proliferation of an immunoglobulin‐secreting B cell clone. AA amyloidosis is a rare complication of chronic inflammation. However, some patients present with diseases combining monoclonal immunoglobulin production and chronic inflammation. The aim of this work was to describe cases of AA amyloidosis associated with monoclonal gammopathies. Patients and methods: We reviewed all patients reported in French national amyloid centres presenting with AA amyloidosis and monoclonal gammopathy and performed a literature review. The quality of AA amyloidosis diagnosis and the causal relationship with monoclonal gammopathy were assessed. Results: In total, four patients from our centres and eight from the literature fulfilled the inclusion criteria. The haematological disorders presenting with monoclonal gammopathy were as follows: Waldenström macroglobulinaemia (n = 8), Schnitzler syndrome (n = 2), multiple myeloma (n = 1) and monoclonal gammopathy of undetermined significance (n = 1). Treatment strategies varied among the cases, with the treatment of the haematological disorder in 4 and anti‐inflammatory treatment in 2. Conclusion: Monoclonal gammopathies might be a rare and poorly known cause of AA amyloidosis. Such monoclonal gammopathies could be named "monoclonal gammopathies of inflammatory significance."